Green synthesis and characterization of metal oxide nanoparticles : Fe (Iron), Cu (Copper), and Zn (Zinc) - Şengönül, Hüseyin. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2023., 2023)
The interest in the green synthesis of nanoparticles has significantly increased in the last decade as an alternative approach to chemical nanoparticle synthesis. Green synthesis is a technique that produces highly valuable materials by minimizing hazardous chemicals and using environmentally friendly, low-cost, and energy and time-saving materials, such as plant-based, industrial wastes, and recycled substances. This study presents the isolation and characterization of quercetin from Prunus serrulata (cherry blossom) and aims to control and understand the synthesis of nanoparticles (iron oxide, copper oxide, and zinc oxide) utilizing Prunus serrulata leaf extract as both reducing and capping agents. The effects of the mixing ratio of the volume of metal ions solution to Prunus serrulata leaf extract, the concentration of metal ions solutions, the pH, and the temperature of the reaction on the synthesis of nanoparticles are examined individually. The characterization of the plantmediated extract is completed through Ultraviolet-Visible Spectroscopy (UV-Vis), Fourier Transform-Infrared Spectroscopy (FT-IR), Liquid Chromatography- Mass Spectrometry (LC-MS), and Nuclear Magnetic Resonance Spectroscopy (NMR). The synthesized nanoparticles were characterized by several instrumental analyses including FT-IR, scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDX), X-ray diffraction (XRD), and X-ray photoelectron spectroscopy (XPS). The optimum conditions for all of the synthesized nanoparticles were determined separately. For Fe3O4 nanoparticles, it follows as: 3:1 (Fe+3 solution:Prunus serrulata leaf extract) mixing ratio, 10 mM Fe+ 3 solution, pH 6, and 25 °C reaction temperature. For CuO nanoparticles, it follows as: 2:1 (Cu+2 solution:Prunus serrulata leaf extract) mixing ratio, 25 mM Cu+2 solution, pH 5, and 25 °C reaction temperature. Finally, for ZnO nanoparticles, it follows as: 2:1 (Zn+2 solution:Prunus serrulata leaf extract) mixing ratio, 25 mM Zn+2 solution, pH 5, and 25 °C reaction temperature.
Keywords: Nanoparticles.; Metallic oxides.; Iron oxides.; Copper oxide.; Zinc oxide.; Green chemistry.